Discerning the adverse effects of psychological therapy: Consensus between experts by experience and therapists. (21st July 2021) - Mc Glanaghy, Edel; Jackson, Jane‐Louise; Morris, Paul; Prentice, Wendy; Dougall, Nadine; Hutton, Paul
Abstract: Measurement of adverse effects of psychological therapy is inconsistent due to ambiguity about the concept. The perspective of people undertaking psychological therapy (that is, experts by experience) has largely been overlooked. This study will investigate whether there is consensus between the opinions of professionals and experts by experience. The Delphi method was used. In Round 1 thematic analysis was used to analyse qualitative responses. Wilcoxon rank‐sum tests were used to examine group differences in Rounds 2 and 3. The study protocol was prospectively registered, reference osf.io/f9wp7. Fifty‐one professionals and 51 experts by experience generated 147 potential adverse effects in Round 1, across 9 themes; including 'therapy amplifies problem', 'emotional lability' and 'sense of self'. Each item was rated for overall consensus in Rounds 2 ( n = 62) and 3 ( n = 63). Thirty‐eight items were rated as essential, very important or important to include on a list of potential adverse effects. A further 12 items were rated as important by the expert by experience group only. Professionals were more conservative in their ratings. There appeared to be consensus between professionals and experts by experience on what to include in a list of adverse effects of psychological therapy (the EDAPT), including novel adverse effects which have not been previously considered. Further research is required to understand which adverse effects are necessary, unnecessary, or indeed harmful to psychotherapy outcomes.